We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
665
3
avatar

What is this equal to? 1+4+9+16+25...

Don't say that it is infinity.

 Jan 13, 2016

Best Answer 

 #1
avatar+23278 
+15

What is this equal to? 1+4+9+16+25...

Don't say that it is infinity.

 

 

\(\begin{array}{lrrrrrrrrrr} & {\color{red}d_0 = 1^2} && 2^2 && 3^2 && 4^2 && 5^2 && \cdots \\ \text{1. Difference } && {\color{red}d_1 = 3} && 5 && 7 && 9 && 11 && \cdots \\ \text{2. Difference } &&& {\color{red}d_2 = 2} && 2 && 2 && 2 && 2 && \cdots \\ \end{array}\)

 

 

\(\begin{array}{rcl} s_n &=& \binom{n}{1}\cdot {\color{red}d_0 } + \binom{n}{2}\cdot {\color{red}d_1 } + \binom{n}{3}\cdot {\color{red}d_2 }\\ s_n &=& \binom{n}{1}\cdot {\color{red}1 } + \binom{n}{2}\cdot {\color{red}3} + \binom{n}{3}\cdot {\color{red}2}\\ \\ \hline \binom{n}{1} &=& n \\ \binom{n}{2} &=& ( \frac{n}{2} ) \cdot ( \frac{n-1}{1} ) \\ \binom{n}{3} &=& ( \frac{n}{3} ) \cdot ( \frac{n-1}{2} )\cdot ( \frac{n-2}{1} ) \\ \hline \\ s_n &=& (n)\cdot {\color{red}1} + ( \frac{n}{2} ) \cdot ( \frac{n-1}{1} )\cdot {\color{red}3} + ( \frac{n}{3} ) \cdot ( \frac{n-1}{2} )\cdot ( \frac{n-2}{1} )\cdot {\color{red}2} \quad | \quad \cdot 6\\ 6\cdot s_n &=& n\cdot 6 + n \cdot ( n-1 )\cdot 9 + n \cdot ( n-1 )\cdot ( n-2 )\cdot 2 \\ 6\cdot s_n &=& n \left[~ 6 + ( n-1 )\cdot 9 + ( n-1 )\cdot ( n-2 )\cdot 2 ~\right] \\ 6\cdot s_n &=& (n) \left[~ 6 + 9n-9 + (n^2 - 3n + 2)\cdot 2 ~\right] \\ 6\cdot s_n &=& (n) \left[~ -3 + 9n + (n^2 - 3n + 2)\cdot 2 ~\right] \\ 6\cdot s_n &=& (n) \left(~ -3 + 9n + 2n^2 - 6n + 4 ~\right) \\ 6\cdot s_n &=& (n) \left(~ 1 + 3n + 2n^2 ~\right) \\ 6\cdot s_n &=& (n) \cdot (n+1) \cdot ( 2n + 1 ) \\\\ \mathbf{s_n} &=& \mathbf{ \frac{ (n) \cdot (n+1) \cdot ( 2n + 1 ) }{6} } \\\\ s_1 &=& 1 = \frac{ 1 \cdot ( 1+1) \cdot ( 2\cdot 1 + 1 ) }{6} = 1\\ s_2 &=& 1+4 = \frac{ 2 \cdot ( 2+1) \cdot ( 2\cdot 2 + 1 ) }{6} = 5\\ s_3 &=& 1+4+9 = \frac{ 3 \cdot ( 3+1) \cdot ( 2\cdot 3 + 1 ) }{6} = 14\\ s_4 &=& 1+4+9+16 = \frac{ 4 \cdot ( 4+1) \cdot ( 2\cdot 4 + 1 ) }{6} = 30\\ s_5 &=& 1+4+9+16+25 = \frac{ 5 \cdot ( 5+1) \cdot ( 2\cdot 5 + 1 ) }{6} = 55\\ \cdots \end{array}\)

 

laugh

 Jan 13, 2016
edited by heureka  Jan 13, 2016
edited by heureka  Jan 13, 2016
 #1
avatar+23278 
+15
Best Answer

What is this equal to? 1+4+9+16+25...

Don't say that it is infinity.

 

 

\(\begin{array}{lrrrrrrrrrr} & {\color{red}d_0 = 1^2} && 2^2 && 3^2 && 4^2 && 5^2 && \cdots \\ \text{1. Difference } && {\color{red}d_1 = 3} && 5 && 7 && 9 && 11 && \cdots \\ \text{2. Difference } &&& {\color{red}d_2 = 2} && 2 && 2 && 2 && 2 && \cdots \\ \end{array}\)

 

 

\(\begin{array}{rcl} s_n &=& \binom{n}{1}\cdot {\color{red}d_0 } + \binom{n}{2}\cdot {\color{red}d_1 } + \binom{n}{3}\cdot {\color{red}d_2 }\\ s_n &=& \binom{n}{1}\cdot {\color{red}1 } + \binom{n}{2}\cdot {\color{red}3} + \binom{n}{3}\cdot {\color{red}2}\\ \\ \hline \binom{n}{1} &=& n \\ \binom{n}{2} &=& ( \frac{n}{2} ) \cdot ( \frac{n-1}{1} ) \\ \binom{n}{3} &=& ( \frac{n}{3} ) \cdot ( \frac{n-1}{2} )\cdot ( \frac{n-2}{1} ) \\ \hline \\ s_n &=& (n)\cdot {\color{red}1} + ( \frac{n}{2} ) \cdot ( \frac{n-1}{1} )\cdot {\color{red}3} + ( \frac{n}{3} ) \cdot ( \frac{n-1}{2} )\cdot ( \frac{n-2}{1} )\cdot {\color{red}2} \quad | \quad \cdot 6\\ 6\cdot s_n &=& n\cdot 6 + n \cdot ( n-1 )\cdot 9 + n \cdot ( n-1 )\cdot ( n-2 )\cdot 2 \\ 6\cdot s_n &=& n \left[~ 6 + ( n-1 )\cdot 9 + ( n-1 )\cdot ( n-2 )\cdot 2 ~\right] \\ 6\cdot s_n &=& (n) \left[~ 6 + 9n-9 + (n^2 - 3n + 2)\cdot 2 ~\right] \\ 6\cdot s_n &=& (n) \left[~ -3 + 9n + (n^2 - 3n + 2)\cdot 2 ~\right] \\ 6\cdot s_n &=& (n) \left(~ -3 + 9n + 2n^2 - 6n + 4 ~\right) \\ 6\cdot s_n &=& (n) \left(~ 1 + 3n + 2n^2 ~\right) \\ 6\cdot s_n &=& (n) \cdot (n+1) \cdot ( 2n + 1 ) \\\\ \mathbf{s_n} &=& \mathbf{ \frac{ (n) \cdot (n+1) \cdot ( 2n + 1 ) }{6} } \\\\ s_1 &=& 1 = \frac{ 1 \cdot ( 1+1) \cdot ( 2\cdot 1 + 1 ) }{6} = 1\\ s_2 &=& 1+4 = \frac{ 2 \cdot ( 2+1) \cdot ( 2\cdot 2 + 1 ) }{6} = 5\\ s_3 &=& 1+4+9 = \frac{ 3 \cdot ( 3+1) \cdot ( 2\cdot 3 + 1 ) }{6} = 14\\ s_4 &=& 1+4+9+16 = \frac{ 4 \cdot ( 4+1) \cdot ( 2\cdot 4 + 1 ) }{6} = 30\\ s_5 &=& 1+4+9+16+25 = \frac{ 5 \cdot ( 5+1) \cdot ( 2\cdot 5 + 1 ) }{6} = 55\\ \cdots \end{array}\)

 

laugh

heureka Jan 13, 2016
edited by heureka  Jan 13, 2016
edited by heureka  Jan 13, 2016
 #2
avatar+105509 
+5

Thanks Heureka for this great answer.

 

I have just noticed that if I right click on your code I can bring it onto the screen in a resizable box.

I can also highlight it  so I assume I can copy it and paste it somewhere else.

This is fabulous!

 

 

Mr Massow has been on  the forum quite a bit recently.  I assume this is one of the improvemtns he has made. :)

Thanks Mr Massow!!    :D

 Jan 13, 2016
 #3
avatar+105509 
0

What is this equal to? 1+4+9+16+25...

Don't say that it is infinity.

 

 

Hang on a moment.

 

If the number of terms is finite then Heureka's formula is great :/  

 

But if the number of terms is not finite, which I think is implied by the dots, then lim as n approaches infinity is infinity

 Jan 13, 2016

15 Online Users

avatar
avatar